1992
DOI: 10.1007/bf02028111
|View full text |Cite
|
Sign up to set email alerts
|

The effects of histamine, pyrilamine, cimetidine, and ranitidine on secretion of lingual lipase and amylase from rat von Ebner's glands

Abstract: Minced von Ebner's glands of rat tongue were incubated in vitro with histamine and histamine receptor antagonists. At various time intervals, media and homogenates of the tissue were assayed for lingual lipase and amylase activity and percentage secretion calculated. Histamine elicited moderate secretion (approximately 10%) of lingual lipase and amylase. In contrast, pyrilamine, an H1 receptor antagonist, elicited > 60% secretion. There were statistically significant differences between the percentage secretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…If exocytosis was the only pathway of secretion, these slopes should have been identical. Similar differences were also seen when the secretion was stimulated by carbachol (12), isoproterenol (12), and histamine (10). The only explanation for these findings is that factors other than exocytosis may be involved in basal or stimulated secretion of these enzymes.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…If exocytosis was the only pathway of secretion, these slopes should have been identical. Similar differences were also seen when the secretion was stimulated by carbachol (12), isoproterenol (12), and histamine (10). The only explanation for these findings is that factors other than exocytosis may be involved in basal or stimulated secretion of these enzymes.…”
Section: Resultssupporting
confidence: 61%
“…To a lesser extent protein secretion from von Ebner's gland is evoked by badrenergic stimulation but not by a-adrenergic stimulation (12). Histamine also stimulates protein secretion from von Ebner's gland (10).…”
Section: Figmentioning
confidence: 95%
See 2 more Smart Citations
“…On the other hand, recent studies have demonstrated that histamine, a powerful stimulant of gastric secretion [2], has a marked secretagogue effect on the exocrine pancreas [3][4][5][6][7][8][9] and on other exocrine secretory glands [10,11]. Exogenous histamine has stimulatory effects on pancreatic secretion in anaesthetised dog [12,13] and rabbit [5,6] and in the isolated dog pancreas [4], but it is less effective in the anaesthetised rat (9).…”
Section: Introductionmentioning
confidence: 99%